2015
DOI: 10.1186/s13048-015-0154-2
|View full text |Cite
|
Sign up to set email alerts
|

MRI for differentiating ovarian endometrioid adenocarcinoma from high-grade serous adenocarcinoma

Abstract: PurposeTo investigate magnetic resonance imaging (MRI) features for differentiating ovarian endometrioid adenocarcinoma (OEC) from high-grade serous adenocarcinoma (HGSC).Materials and methodsTwenty-three patients with 25 OECs and 93 patients with 139 HGSCs confirmed by surgery and pathology underwent conventional MRI and diffusion-weighted imaging (DWI). The MRI features of the tumors, including laterality, size, shape, configuration, signal intensity, ADC value of solid component, enhancement, ascites, synch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…TIC has been applied in the differential diagnosis of breast, prostate, ovary and other lesions, suggesting that all benign tumors had type I, the majority of malignant tumors had type III, only a small number of them had type II, and none had type I; type III TIC appeared to be specific for malignant tumors and was never observed in benign tumors [ 26 , 27 ]. Our study showed that type III TIC outnumbered type II considerably, which was in accordance with the previous literatures [ 28 , 29 ]. Moreover, compared with EOCs with curve type II TIC, EOCs with type III demonstrated significantly higher histological grade, MVD, VEGF expression, Ki67-positive cells and serum CA125 level, indicating a poor prognosis due to its high but immature neovascularization, low differentiation and active proliferative capacity.…”
Section: Discussionsupporting
confidence: 94%
“…TIC has been applied in the differential diagnosis of breast, prostate, ovary and other lesions, suggesting that all benign tumors had type I, the majority of malignant tumors had type III, only a small number of them had type II, and none had type I; type III TIC appeared to be specific for malignant tumors and was never observed in benign tumors [ 26 , 27 ]. Our study showed that type III TIC outnumbered type II considerably, which was in accordance with the previous literatures [ 28 , 29 ]. Moreover, compared with EOCs with curve type II TIC, EOCs with type III demonstrated significantly higher histological grade, MVD, VEGF expression, Ki67-positive cells and serum CA125 level, indicating a poor prognosis due to its high but immature neovascularization, low differentiation and active proliferative capacity.…”
Section: Discussionsupporting
confidence: 94%
“…The possible reason may be that Type II cancer comprised of only one pathological subtype, while there were four subtypes identified in Type I OEC patients resulting in much heterogeneity in the lesion. Also, previous research found that hyperintense cystic components were often detected on T1WI in clear cell and endometroid ovarian cancer than in other subtypes [29, 30]. These findings are supported by our study.…”
Section: Discussionsupporting
confidence: 92%
“…In recent years, considerable advances have been achieved in the understanding and identification of the underlying pathogenesis in different subtypes [ 1 , 14 ]. Our previous study showed that conventional MRI combining DWI may be helpful for differentiating ovarian endometrioid carcinomas from HGSC [ 15 ]. Previous studies have indicated that there are different risk factors, origins, genetic alterations, biological behaviors, clinicopathological characteristics and chemotherapy sensitivities between ovarian CCC and HGSC [ 2 6 , 16 ].…”
Section: Discussionmentioning
confidence: 99%